2009
DOI: 10.1891/0886-6708.24.3.302
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Risk Factors of Physically Forced and Alcohol- or Other Drug-Enabled Sexual Assault Among University Women

Abstract: The Campus Sexual Assault Study examined whether undergraduate women's victimization experiences prior to college and lifestyle activities during college were differentially associated with the type of sexual assault they experienced: physically forced sexual assault and incapacitated sexual assault. Self-reported data collected using a Web-based survey administered to more than 5,000 undergraduate women at two large public universities indicated that victimization experiences before college were differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 32 publications
7
85
0
2
Order By: Relevance
“…However, Krebs, Lindquist, Warner, Fisher, and Martin (2009) estimated the prevalence of IPV among a sample of women attending two predominantly White colleges and universities in the CSA study. Although the time period and wording of the questions is slightly different from what was used in the current study, the comparison is striking.…”
Section: Discussionmentioning
confidence: 99%
“…However, Krebs, Lindquist, Warner, Fisher, and Martin (2009) estimated the prevalence of IPV among a sample of women attending two predominantly White colleges and universities in the CSA study. Although the time period and wording of the questions is slightly different from what was used in the current study, the comparison is striking.…”
Section: Discussionmentioning
confidence: 99%
“…The research methods used in the present study were also used to collect data on sexual assault from 5,446 undergraduate women at two non-HBCUs in 2005 and 2006. A response rate of 42% was achieved at the non-HBCUs, and comparisons are made in this article between the HBCU and non-HBCU women (Krebs et al, 2009a(Krebs et al, , 2009b.…”
Section: Recruitment Of the Study Samplementioning
confidence: 95%
“…There were larger percentages of seniors (28.3%) and juniors (24.6%) than freshmen (23.2%) and sophomores (20.8%) in the sample. Descriptive data on the non-HBCU sample can be found in other publications (Krebs et al, 2009a(Krebs et al, , 2009b.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, self-blame, posttraumatic stress disorder, maladaptive adjustment, alcohol/drug-related coping strategies, and social withdrawal are all consequences of early victimization and similarly predict later adult revictimization (e.g., Krebs, Lindquist, Warner, Fisher, & Martin, 2009;Miller, Markman, & Handley, 2007). Some scholars have suggested that women with victimization histories are increasingly vulnerable to adult revictimization due to deficits in information processing, behavioral cue recognition, and less assertive response strategies when in sexually dangerous situations (Breitenbecher, 1999;Gidycz, McNamara, & Edwards, 2006;VanZileTamsen, Testa, & Livingston, 2005;Wilson et al, 1999).…”
Section: Prior Victimizationmentioning
confidence: 99%